Cognitive functioning in individuals with Parkinson's disease and traumatic brain injury: A longitudinal study. (September 2016) - Schiehser, Dawn M.; Filoteo, J. Vincent; Litvan, Irene; Pirogovsky-Turk, Eva; Lessig, Stephanie L.; Song, David S.
Abstract: Objective: To examine longitudinal changes in cognition in individuals with Parkinson's disease (PD) with and without a history of traumatic brain injury (TBI). Methods: Twenty-five PD participants with a history of mild-moderate post-acute (>9 months) TBI and 25 demographically-matched PD controls without a history of TBI were administered measures of cognition (Mattis Dementia Rating Scale), mood, and motor functioning at baseline and at a two-year follow-up evaluation. Results: Individuals with PD and a history of TBI evidenced significantly greater decrements in overall cognition over the two year follow-up period compared to those without a history of TBI. Secondary subscale analyses suggest cognitive decrements may be mainly in the area of executive function, while a trend for group differences on the memory subscale was also observed. Groups did not differ on demographic, motor function, disease severity, cognitive, and mood profiles at baseline and evidenced comparable changes in mood and motor symptoms from baseline to follow-up. Conclusion: Findings suggest that a history of mild-moderate TBI is a risk factor for cognitive decline in individuals with PD. Highlights: PD + TBI individuals evidence greater cognitive decline than PD patients without TBI. In PD + TBI, cognitive decrements may be mainly in the area of executive function. TBI is a risk factor for cognitive decline in individuals with PD.